Mediterranea : Art Contemporain des pays mediterranées. - Abousleiman; Bartolo, Adrian; Baudson, Michel; Beaugrand, Catherine; Belkahia, Farid; Bertazzoni, Giovanna; Butor, Michel; Carron, Mórag Mc.; Dumortier, Georges; Eviner, Inci; Garau, Salvatore; Gorreri, Simonetta; et al. (Brussel : Artlife for the World - Contemporary art events, 1998)
Beaugrand, Abousleiman : Catherine ; Belkania, Farid ; Camilleri, Austin ; Dahdaleh, Ghada ; Deguara, Savio ; Eviner, Inci ; Garau, Salvatore ; Hassan, Fathi ; Kachri, A. ; Kandilaptis, Babis ; Khattari, Majida ; Koraichi, Rachid ; Lefkochir, Costa ; Loizidou, Maria ; Lopez-Menchero, Emilio ; Mondino, Aldo ; Niati, Laila MuraywidHouria ; Okasha ; Onur, Füsun ; Samakh, Erik ; Saouli, Salah ; Sari, Abdennasser ; Schaerf, Eran ; Schwarzberg, Shlomo ; Seguso, Livio ; Shafik, Medhat ; Shawa, Laila ; Tabbaa, Samer ; Theodoulos, Gregoriou
biografie
Mediterranea : Art contemporain des pays méditerraneens / Contemporary art of the Mediterranean countries, Brussel, 29.9. - 15.11.1998
Engels
Frans
Frans & Engels
boek
Keywords: Middellands zeegebied